Tinjauan Implementasi Fatwa DSN-MUI Tentang Digital Fundraising Zakat: Studi Kasus Baznas Kota Bandung - Rika Safitri; Qoorie Handayani Asysyabani; Ahmad Fauzan; Fahri Rizwar; Jaenudin Jaenudin (J-Alif : Jurnal Penelitian Hukum Ekonomi Syariah dan Budaya Islam, 2026)
The development of digital technology has transformed the practice of zakat collection in Indonesia, yet its implementation still faces challenges related to Sharia compliance and governance. Fatwa DSN-MUI No. 116/DSN-MUI/IX/2017 provides a normative foundation for digital zakat fundraising, but few studies have examined its compatibility with the practices of zakat management institutions, particularly the National Zakat Agency (BAZNAS) at the local level. This study employs a descriptive, empirical juridical method to validate the alignment between the Sharia norms in the fatwa and the operational practices of digital fundraising at BAZNAS Bandung City, using interviews and internal document review. The findings show that BAZNAS has implemented the akad wakalah bil ujrah (agency contract with a fee) in digital zakat transactions and has integrated its systems through the SIMBA application. However, obstacles remain, including uneven digital literacy, non-real-time payment gateway integration, and suboptimal special auditing for digital aspects. These findings underscore the need to improve digital-Sharia literacy, strengthen technological infrastructure, establish strategic collaboration with Sharia fintech, and standardize Sharia auditing for digital systems in order to enhance accountability and Sharia compliance in digital zakat collection.